2019
DOI: 10.1111/jcmm.14605
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of exemestane as a novel chemotherapy for gastric cancer

Abstract: CYP19A1/aromatase (Ar) is a prognostic biomarker of gastric cancer (GCa). Ar is a critical enzyme for converting androstenedione to oestradiol in the steroidogenesis cascade. For decades, Ar has been targeted with Ar inhibitors (ARIs) in gynaecologic malignancies; however, it is unexplored in GCa. A single‐cohort tissue microarray examination was conducted to study the association between Ar expression and disease outcome in Asian patients with GCa. The results revealed that Ar was a prognostic promoter. Bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…16 Targeting the steroidogenic enzyme cytochrome CYP450 19A1 (aromatase) with exemestane can be effective for patients with GCa. 17 Study shows that differential levels of LDLR expression in EOC cells determine the platinum sensitivity in an LDLR-dependent manner. 10 LDLR expression reprogrammes cellular transcriptome associated with lipid metabolism (Lands cycle in LD) to be the mechanism underlying cisplatin sensitivity.…”
Section: Introductionmentioning
confidence: 86%
“…16 Targeting the steroidogenic enzyme cytochrome CYP450 19A1 (aromatase) with exemestane can be effective for patients with GCa. 17 Study shows that differential levels of LDLR expression in EOC cells determine the platinum sensitivity in an LDLR-dependent manner. 10 LDLR expression reprogrammes cellular transcriptome associated with lipid metabolism (Lands cycle in LD) to be the mechanism underlying cisplatin sensitivity.…”
Section: Introductionmentioning
confidence: 86%
“…Wang et al showed that CYP1A1 was a possible new molecular target for GC therapy ( 34 ). Yang et al found that CYP19A1 was a prognostic biomarker of GC ( 35 ). Ma et al showed that high CYP1A1 expression may be a favorable factor for patients with GC ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Threshold value (Ct) dynamics were used (2 −ΔΔCt ) for the quantitation of gene expression. The qRT‐PCR primer sequences used were as follows 20 : CYP19A1 forward 5′‐ACC CTT CTG CGT CGT GTC A‐3′, reverse 5′‐TCT GTG GAA ATC CTG CGT CTT‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…The WST-1 assay was used for assessing cell growth. 24 Briefly, 2.5 × 10 3 cells/well were seeded in 96-well plates with RPMI/10% fetal bovine serum (FBS) and were incubated for 24 h. The drugs were then added following previous work, 20 and the cells were further incubated (single treatment: UA [20,40,60, 80, and 100 μM] and 5-FU [10 μM]). After 48 h of incubation, 1:10/v:v of WST-1 (Roche) solution was added for a further 60-min incubation period, after which the cell viability was measured through colorimetric detection with an ELISA plate reader (BECKMAN COULTER PARADIGM TM Detection Platform) at an absorbance of 450 nm to generate an optical density proportional to the relative abundance of live cells in the given wells.…”
Section: Cytotoxic Analysis and Ic50 Calculationmentioning
confidence: 99%